PEDIATRIC REFERENCE ANATOMY FOR ANTEROLATERAL LIGAMENT RECONSTRUCTION– A CADAVERIC STUDY. Issue 4 (28th April 2020) - Randhawa, Sahej D; Trivedi, Sunny; Stavinoha, Tyler J.; Ganley, Theodore J.; Tompkins, Marc; Shea, Kevin G.
Background: The anatomy of the anterolateral ligament (ALL) has been controversial, with modern studies varying in their description of the precise origin and insertion, as well as relation to surrounding structures on the lateral femur and anterolateral tibia Regardless of such controversy, principles of reconstruction, even non-anatomic, require a clear understanding of the referenced anatomy and surrounding structures. Due to high rates of primary and recurrent ACL tears in pediatric/adolescent patients, the use of ALL reconstruction is increasing in these groups. No pediatric cadaveric study to date has clearly identified the locations of the known surrounding structures of the anterolateral ligamentous complex. Purpose: The purpose of this study was to quantitatively assess the anatomy of the pediatric lateral collateral ligament (LCL) origin, the popliteus origin, and in the tibial insertion of the iliotibioband (ITB). Methods: Nine pediatric cadaveric knee specimens were dissected to identify the ligamentous femoral origin of the LCL, popliteus, and tibial insertion of the ITB.. Marking pins were used to localize the central footprint of these structures, followed by CT Scans. Results: LCL & Popliteus: On the femur, the popliteus was consistently found deep to the LCL and inserted both distally and anteriorly to the LCL a mean distance of 4.6 mm (range 1.9 to 7.6 mm; std dev 2.0). The LCL measured a mean of 12.5 mm to the joint line while the popliteus measured a mean of 8.2 mm from the joint line. Both the LCL and popliteus were consistently distal to the physis. The LCL was a mean distance of 4.4 mm (range 1.0 - 9.5 ) and the popliteus was a mean distance of 8.2 (range 1.7 – 12.5), respectively.ITB insertion: The ITB insertion at Gerdy's tubercle had an average footprint measuring 28.2 mm 2 (range 10.3-58.4), and the ITB center was found proximal to the physis in 6 specimens and distal in 3 specimens. Mean distance from the footprint center to the physis was 1.6 mm proximal (range 7.1 mm proximal to 2.2 mm distal). Conclusion: This study provides quantitative anatomy to structures on the lateral femur and anterolateral tibia, commonly referenced in descriptions of the ALL and lateral extraarticular reconstruction techniques. Knowledge of these structures will define the anterolateral complex and guide extra-articular procedures that provide extraarticular anterolateral rotatory stabilization in the pediatric patients. : Figure 1. CT specimen with markers indicating the femoral origin of the LCL and popliteus. Relation to the physis and cartilaginous articular surface are clearly identified. Figure 2. 3D CT rendering, recreating an effective true lateral radiograph of the knee. Red dots on markers identify point of penetration into the lateral cortex of the distal femur.